Examination of phylogenetic relationship and sexual dimorphism in the Vietnam warty newt (Paramesotriton deloustali (Bourret, 1934)) in Vietnam - Nguyen, Thinh Van; Nguyen, Thien Tao; Hai, Ngo Ngoc; Ninh, Hoa Thi; Nguyen, Huy Quoc; Pham, Cuong The; Nguyen, Truong Quang; Bernardes, Marta; Ziegler, Thomas (Vietnam Journal of Biotechnology, 2024)
Two warty newt species, Paramesotriton deloustali and P. guangxiensis, are known from Vietnam for a long time. However, the taxonomic status of some Vietnamese populations was recently clarified. In this study, we conducted surveys in northern Vietnam to collect samples for molecular and morphological analyses of Paramesotriton species. Our phylogenetic analyses based on two mitochondrial genes (16S and ND2) agreed well with previous findings that populations from Bac Kan, Ha Giang, Lao Cai, Son La and Vinh Phuc provinces were regarded as P. deloustali, and populations from Cao Bang and Quang Ninh provinces were identified as P. guangxiensis. Regarding sexual dimorphism, it is a prevalent phenomenon in many salamanders, including P. deloustali. There exists a female-biased pattern of size dimorphism with longer snout-vent length and trunk length in females than in males of P. deloustali. On the other hand, a male-biased pattern is documented for cloaca sizes. Furthermore, only males display a unique color of light green on the lateral sides of the tail.